DIDACTIC AND GAME METHODS IN EXTRACURRICULAR WORK IN THE NATIVE LANGUAGE IN ELEMENTARY SCHOOL - Madaminova Samidabonu Umidovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the topical topic of the use of didactic and game methods in the native language in extracurricular time. Didactic play and game methods help to make the educational material fascinating, create a joyful working mood. Positive emotions facilitate the process of cognition. In the didactic game, such conditions are created in the lessons of the Russian language in which each child gets the opportunity to act independently in a certain speech situation, with certain phenomena and facts of the language, acquiring his own effective and sensual experience.